Effect of Sucrose as Carbon Source and Probiotic Administrations on Bacterial Population Dinamic and Water Quality in White Shrimp, Litopenaeus vannamei Culture - Sukenda, .; Hadi, P.; Harris, E. (Indonesian Society of Scientific Aquaculture (ISSA), 2006)
Disinfection and nutrient enrichment prior stocking of post larvae in the pond will be affected on the growth and composition of microbe. Attention should be taken to some factors related to deterministic and stochastic factors of aquaculture environment in order to develop microbe community. This study was performed to determine effect of sucrose and probiotic supplementation to shrimp culture pond on water quality profile and population dynamic on shrimp culture media. The treatments were supplementation of sucrose as carbon source, probiotic, and sucrose + probiotic into 25 L culture medium containing white shrimp, Litopenaeus vannamei. Shrimp were fed commercial diet containing 30% protein by 5% body weight every day. The result of study showed that bacterial population was increased by increasing time of shrimp rearing. Increased of bacterial population was contrary to DO value. Bacteria grew was heterotrop and vibrio that its intensity varied during experiment. Supplementation of sucrose supported proliferation of bacteria including heterotrop, probiotik and vibrio groups. Specifically, interaction between probiotic bacteria and vibrio was also found. The presence of probiotic bacteria showed a negative impact on vibrio population. Further, development of bacteria in general was also implicated to fluctuation of ammonia concentration in pond. Keywords: carbon, sucrose, probiotic, white shrimp, Litopenaeus vannamei ABSTRAK Kegiatan disinfeksi dan pengkayaan nutrien sebelum penebaran PL akan mempengaruhi pola pertumbuhan dan komposisi mikroba di tambak. Hal-hal yang perlu diperhatikan dalam pengembangan komunitas mikroba adalah faktor-faktor deterministic dan sthocastic masing-masing lingkungan budidaya. Penelitian ini dilakukan untuk mengetahui pengaruh pemberian bahan berkarbon (sukrosa) dan probiotik di tambak terhadap profil kualitas air serta dinamika populasi pada perairan budidaya. Pada penelitian ini dilakukan penambahan sumber karbon (sukrosa), penambahan probiotik dan penambahan sukrosa + probiotik pada masing-masing wadah yang berisi 25 liter air dan udang Vanamei, Litopenaeus vannamei. Pakan yang diberikan berupa pellet komersial dengan kadar protein 30% setiap hari sebanyak 5% dari biomassa awal. Dari hasil penelitian ini diketahui bahwa populasi bakteri pada media budidaya meningkat seiring dengan bertambahnya waktu pemeliharaan. Peningkatan jumlah populasi bakteri ini diikuti oleh semakin menurunnya nilai DO secara umum. Selain bakteri heterohof, tumbuh juga bakteri golongan Vibrio dengan persentase kemunculan yang berbeda pada setiap perlakuan. Penambahan sukrosa dalam media budidaya mendukung proliferasi bakteri secara umum, heterotrof, probiotik dan golongan Vibrio. Secara spesifik, timbul juga interaksi antara bakteri probiotik dengan bakteri Vibrio. Tumbuhnya bakteri probiotik berimplikasi negatif terhadap populasi Vibrio. Selain itu pertumbuhan bakteri secara umum juga berimplikasi terhadap fluktuasi kadar amonia perairan. Kata kunci : karbon, sukrosa, probiotik, udang vaname, Litopenaeus vannamei